The velar animal prefix relic in Vietnam languages - Smith, Kenneth D. (2024)
Benedict (1972) and Matisoff (1973a.25 (footnote 37), 1973b)1 have discussed a Tibeto—Burman bound velar animal prefix. It is the purpose of this paper to investigate the possibility that the animal prefix may have been a Southeast Asian areal phenomenon by examining linguistic data from Vietnam. There will be two aspects to this study. Section 1 is an in—depth study of one language, Sedang (a North Bahnaric language of the Mon—Khmer family), to see if a velar component is more frequent in animal names than in the general vocabulary of the language. Section 2 is a look at twenty-one animal terms in 26 different languages of Vietnam to see if there is any evidence for the prefix which such a comparative study might reveal. Section 3 lists all Sedang animal names in which there is a non-final k.